Discussion on "Zemn-al-lafz" and "Tarjomat-al-lafz" Figurative Devices Based on the Text of the Manuscript of " Rasa'il al-Ijaz " - Maryam Afzali; Ahmad Amiri Khorasani; Mohammad Sadeq Basiri (مطالعات زبانی و بلاغی)
One of the prose works of Amir Khosrow Dehlavi is the valuable book "Rasa'il al-Ijaz", which was written in the early eighth century AH. The author, while using a lot of literary figurative devices in the text of the work, has dedicated its third treatise to rhetoric. In this sector, he has taken over some past figurative of the device and some figurative of the device in this sector, are made by Amir Khosrow himself, which shows his mastery and knowledge in this field. Ambiguity or imagination is one of the literary figurative devices that has a special place in this valuable work. Observance of verbal proportion and also the ambiguity of proportion have a great role in this text. The abundant use of some special and rare figurative devices, such as "Tarjomat-al-lafz" and "Zemn-al-lafz" in this work, which according to the author claims, is one of his innovations, in line with the purpose of observing proportionality, is remarkable; But with a little care and comparison with other rhetorical books, we find that these figurative of devices are sometimes mixed with some similar industries, and some of them existed before Amir Khosrow with a slight difference, and their basis in previous rhetorical books, Been. Considering the importance and position of this work in the field of literary works of technical and artificial prose, the authors in this study, while examining the place of ambiguity in this work, critique and analyze some of its new figurative devices, such as "Tarjomat-al-lafz" and "Zemn-al-lafz".